The immune receptor XA21 causes semi-male sterility and grain loss in rice - de Toledo Franceschi, Beatriz; Vergish, Satyam; Singh, Yatendra; Li, Jian-Liang; Shamsunnaher,; Ding, Gao-Lu; Chen, Sixue; Song, Wen-Yuan (Frontiers in Plant Science, 2025)
As part of an armory against pathogens, plants carry resistance (R) genes despite the fitness costs they can incur. While these detrimental effects have been associated with the presence and interactions of numerous R genes in various plant species, molecular models do not exist for the mechanisms underlying R gene-mediated fitness costs. The rice R gene Xa21, encoding a cell-surface immune receptor, specifies robust resistance to Xanthomonas oryzae pv. oryzae. Here, we demonstrate that Xa21 expression causes drastic fertility defects, including reduced pollen viability, impaired anther dehiscence, and severe grain loss, at a low temperature (24°C) and in a dose-dependent manner. Under such growth conditions, Xa21 plants displayed abundant accumulation of reactive oxygen species in their anthers and decreased expression of genes related to jasmonate biosynthesis, signaling, and response in their spikelets during anthesis. Consequently, jasmonate contents in XA21 spikelets were lower than those in the control. The exogenous application of methyl jasmonate largely rescued the anther dehiscence of Xa21 plants. Given the key roles of lipid-derived jasmonates in stamen development and maturation in plants, our findings link R gene expression, jasmonic acid (JA) signaling, and fertility defects; identify temperature as an environmental factor influencing the range of R gene functions; and explain the abundant accumulation of 17 transposable-like elements previously observed in the Xa21 locus.